2017
DOI: 10.1177/0312896217708227
|View full text |Cite
|
Sign up to set email alerts
|

Board independence and the variability of firm performance: Evidence from an exogenous regulatory shock

Abstract: We use the 2003 NYSE and NASDAQ listing rules for board independence as an exogenous shock to estimate the causal relation between board independence and the variability of firm performance. Using a difference-in-difference approach, we find that non-compliant firms without a majority of independent directors observe a larger decrease in the variability of firm performance than compliant firms. In particular, board independence is negatively associated with the variability of (1) monthly stock returns, (2) ROA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…Articles have looked at R&D valuation (Chen et al, 2018), investments in R&D (Hamada, 2017) and market orientation (Bucic et al, 2017). Other topics that have recently attracted attention in the AJM include research on the board of directors as well as decision making with regard to investments (He et al, 2018; Hutcheson and Newell, 2018), bank locations (Heard et al, 2018) and the effects of board independence on decision making (Bird et al, 2018). The influence of the 2015 Qualitative Finance Special Issue is also visible in this map through the bursts in topics such as culture, employment and pension (i.e.…”
Section: Towards a Systematic Reviewmentioning
confidence: 99%
“…Articles have looked at R&D valuation (Chen et al, 2018), investments in R&D (Hamada, 2017) and market orientation (Bucic et al, 2017). Other topics that have recently attracted attention in the AJM include research on the board of directors as well as decision making with regard to investments (He et al, 2018; Hutcheson and Newell, 2018), bank locations (Heard et al, 2018) and the effects of board independence on decision making (Bird et al, 2018). The influence of the 2015 Qualitative Finance Special Issue is also visible in this map through the bursts in topics such as culture, employment and pension (i.e.…”
Section: Towards a Systematic Reviewmentioning
confidence: 99%
“…Board independence has been widely acknowledged as an effective mechanism for monitoring corporate insiders and prevents firms from suffering from severe managerial agency problems (e.g. Bird et al ., ; Claessens and Yurtoglu, ; Cumming et al ., ; Fauver et al ., ; Meng et al ., ). Outside directors often are well‐known business and accounting professionals, and their concern for their reputation will increase their incentive to intervene in corporate investment policy at central SOEs.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The literature has discussed how to constrain the corporate overinvestment problem stemming from the abuse of rights by controlling shareholders. Such methods include increasing the cash flow rights of the controlling shareholders (La Porta et al ., ) and enhancing oversight by independent directors (Lu and Wang, ; Bird et al ., ) or by multiple large shareholders (Jiang et al ., ). However, few studies have examined the potential governance role induced by internal governance improvement aimed at controlling shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this widespread belief in the importance of corporate governance mechanisms for resolving agency problems, the empirical literature investigating the individual effect of corporate governance mechanisms on corporate value has not been able to consistently identify positive effects on performance (Larcker et al ., ). More recent papers highlight the importance of measures of performance (Bird et al ., ) and the endogeneity challenges (Tan et al ., ). Nguyen and Rahman () found that governance structures can reduce this agency conflict and that ‘board compensation and ownership concentration increase the likelihood of a divestiture’.…”
Section: Previous Literature and Hypothesis Developmentmentioning
confidence: 99%